Quality of Life of Oral Squamous Cell Carcinoma Patients before and after Primary Treatment - Renu Yadav; Rahul B Patil; Dhiraj K Umbare; Akhilesh Vajpayee; Pranay R Thakur; Isha Chauhan (Wolters Kluwer Medknow Publications, 2023)
Background: HNSCC (head and neck squamous cell carcinoma) is a serious global health problem, with estimated more than 550,000 new cases and 300,000 deaths annually. More than 90% of these malignancies are oral squamous cell carcinoma (OSCC). Materials and Methods: Patients selected were asked to fill the detailed structured case history proforma and thorough clinical examination, structured, pre-designed, pre-evaluated (UW-QOL) UW Questionnaire version 4 on quality of life (QOL) of oral squamous cell carcinoma patients containing thirteen subjective questionnaires and three global questionnaires. All the patients of OSCC after one month (1 month) of radiation and chemotherapy were assessed for quality of life by questionnaire. Result: Post-treatment QOL assessment of OSCC patients reveals a number of problems such as chewing, swallowing, saliva, lack of activity, and mood disturbances. Preoperative clinical features including tumor site, tumor stage, and extent of mouth opening have a significant impact on post-treatment problems in different ways. Conclusion: The need to balance clinician's need and use of health-related quality of life (HRQOL) data against patient's burden should be considered in the selection process.